Hubungan Kadar Hematokrit dan Tekanan Darah pada Subjek Laki-laki Perokok Usia Dewasa Muda - Isa, Roi O.; Rotty, Linda W.A.; Polii, Efata B.I. (e-CliniC, 2017)
Abstract: Smoking is a major health problem in Indonesia especially in adult males. The age of a person to initially start smoking becomes younger, therefore, the prevalence of smoking in Indonesia has increased in 2013 (36.3%) compared to that in 2007 (34.2%). Smoking is a risk factor for a number of chronic diseases such as cancer, lung diseases, and cardiovascular diseases. Several previous studies had suggested a relationship between hematocrit levels, blood viscosity and blood pressure. This study was aimed to determine the correlation between hematocrit level and blood pressure in young adult male smokers as subjects. This was an analytical study with a cross-sectional design. Blood pressure and hematocrit level were performed on a total of 40 male students of the Faculty of Engineering Sam Ratulangi University Manado. Data were analyzed statistically by using the Spearman correlation test. The correlation test on the relationship between blood hematocrit level and systolic blood pressure showed an r value of 0.236 and a P value of 0.143 while the correlation test on the relationship between blood hematocrit level and diastolic blood pressure resulted in an r value of 0.352 and a P value of 0.026. Conclusion: There was a positive correlation between hematocrit level and diastolic blood pressure in young adult smokers but not for systolic blood pressure.Keywords: smokers, hematocrit, blood pressureÂ Abstrak: Merokok menjadi masalah kesehatan utama di Indonesia khususnya pada kaum lelaki dewasa. Usia seseorang mulai merokok semakin muda dan prevalensi merokok di Indonesia mengalami peningkatan pada tahun 2013 (36,3%) dibandingkan tahun 2007 (34,2%). Merokok sebagai faktor risiko sejumlah penyakit kronis seperti kanker, penyakit paru-paru, dan penyakit kardiovaskuler. Beberapa penelitian sebelumnya menyatakan adanya hubungan antara kadar hematokrit, viskositas darah, dan tekanan darah. Penelitian ini bertujuan untuk mengetahui hubungan kadar hematokrit dan tekanan darah pada subjek laki-laki perokok usia dewasa muda. Jenis penelitian ialah analitik dengan desain potong lintang. Subyek penelitian ialah 40 orang mahasiswa laki-laki Fakultas Teknik Universitas Sam Ratulangi Manado. Pemeriksaan tekanan darah dan hematokrit darah dilakukan terhadap seluruh subyek. Analisis statistik menggunakan uji korelasi Spearman. Hasil uji korelasi pada hubungan kadar hematokrit dengan tekanan darah sistolik (TDS) mendapatkan nilai r=0,236 dan nilai P =0,143 sedangkan pada hubungan kadar hematokrit dengan tekanan darah diastolik (TDD) didapatkan nilai r=0,352 dan nilai P=0,026. Simpulan: Terdapat hubungan positif antara kadar hematokrit dan tekanan darah diastolik pada perokok laki-laki usia dewasa muda tetapi tidak berlaku untuk tekanan darah sistolik.Kata kunci: perokok, hematokrit, tekanan darah